Contextualizing the gender gap in voter turnout. (15th March 2022) - Stauffer, Katelyn E.; Fraga, Bernard L.
ABSTRACT: Overall women turn out to vote at a higher rate than men, yet few studies have examined the consistency of this finding across American electoral contexts. We use voter file data to compare turnout for men and women at the national-, state-, and district-level from 2008 to 2018, focusing on variation in the gender turnout gap by electoral competition, candidate gender, and race and ethnicity. While we find no relationship between women candidates and the turnout gap, we do find that the gap is largest in presidential election years, and shrinks in the most competitive congressional districts. Most importantly, however, we highlight the critical role of race/ethnicity in our understanding of the nature and contours of the turnout gap, adding to the growing body of scholarship calling for an intersectional approach to the study of political participation.